The accumulation of harmful genes within the ROH hotspot regions of the Tibetan sheep genome does not lead to genetic load - Lixia Sun; Chao Yuan; Tingting Guo; Yaqin Bai; Zengkui Lu; Jianbin Liu (BMC Genomics)
Abstract Background Prolonged natural selection and artificial breeding have contributed to increased uniformity within the Tibetan sheep population, resulting in a reduction in genetic diversity and the establishment of selective signatures in the genome. This process has led to a loss of heterozygosity in specific genomic regions and the formation of Runs of Homozygosity (ROH). Current research on ROH predominantly focuses on inbreeding and the signals of selection; however, there is a paucity of investigation into the genetic load and selective pressures associated with ROH, both within these regions and beyond. On one hand, genes located situated ROH hotspot regions exhibit a degree of conservation in their genomic segments; on the other hand, these regions may also serve as critical loci for identifying signals of selection. Results High-throughput re-sequencing technology was utilized to investigate the ROH hotspot regions across 11 Tibetan sheep populations, resulting in the identification of ten conserved genes (ARHGEF16, Tom1l2, PRDM16, PEMT, SREBF1, Rasd1, Nt5m, MED9, FLCN, RAI1) that are associated with lipid metabolism, lactation, and development. These genes exhibited highly conserved within the ROH hotspot regions across all Tibetan sheep populations. Employing the integrated haplotype score (iHS) method, we screened for selective sites within frequently observed ROH hotspot regions to elucidate genomic differences among Tibetan sheep populations. A comprehensive analysis was conducted, involving Rnhom, dN/dS ratios, missense/synonymous ratios, and loss-of-function (LOF)/synonymous ratios, to investigate the accumulation of deleterious genes and the associated genetic load both within and outside ROH hotspot regions. The results revealed a higher accumulation of deleterious genes and a reduced genetic load within the ROH regions. Conclusions This study provides a comprehensive and precise genomic analysis and interpretation of Tibetan sheep, offering theoretical basis for genetic breeding and evolution in Tibetan sheep.